Sociological Analysis of Informal Social Control and Juvenile Delinquency in Pandu Village, Manado City - Aurekeren Muntu; Ferdinand Kerebungu; Hamsah Hamsah (DISCOURSE: Indonesian Journal of Social Studies and Education, 2026)
This study aims to sociologically analyze the dynamics of juvenile delinquency in Pandu Village, Manado, by situating the phenomenon within the broader structure of social relations that shape adolescents’ lives. Drawing on social control theory and the concept of collective efficacy, this research employs a qualitative case study design to examine how informal social institutions regulate deviant behavior. Data were collected through in-depth interviews and field observations and were analyzed thematically to identify patterns of social interaction influencing adolescent behavior. The findings indicate that juvenile delinquency cannot be understood merely as an individual problem, but rather as a reflection of the configuration of local social structures. Three major findings emerged. First, strengthened family-based social control—through emotional attachment, open communication, and moral exemplification—serves as the primary protective mechanism. Second, the institutionalization of religious values functions as a moral foundation within the community, reinforcing the legitimacy of social norms. Third, local social cohesion fosters collective supervision, thereby limiting opportunities for anonymity and deviant conduct. The integration of these three dimensions forms a relatively stable and resilient informal social control system against delinquency risks. This study reinforces the relevance of social control theory and collective efficacy within the context of local Indonesian communities. Practically, the findings suggest that preventing juvenile delinquency is more effective when focusing on strengthening family institutions, revitalizing religious participation, and enhancing community solidarity rather than relying solely on punitive approaches. However, this study is limited to a single-site qualitative case; therefore, future research employing comparative or mixed-method designs is recommended to test the consistency of these findings across different social contexts, including communities with higher levels of urbanization and social disorganization.